To solve the equation \((x−1)(2x+5)=0\) using the Zero Product Property, we set each factor equal to zero and solve for \(x\):
-
Set the first factor equal to zero: \[ x - 1 = 0 \] Solving for \(x\) gives: \[ x = 1 \]
-
Set the second factor equal to zero: \[ 2x + 5 = 0 \] Solving for \(x\) gives: \[ 2x = -5 \implies x = -\frac{5}{2} \]
So the values of \(x\) that make the quadratic equation equal zero are \(x = 1\) and \(x = -\frac{5}{2}\).
The correct response is: The quadratic equation will equal zero when \( x \) equals negative \( \frac{5}{2} \) and \( x \) equals 1.